2020
DOI: 10.1186/s13014-020-01544-0
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastasis and local ablation in the era of systemic targeted and immunotherapy

Abstract: Background: During these last years, new agents have dramatically improved the survival of the metastatic patients. Oligometastases represent a continuous field of interest in which the integration of metastases-directed therapy and drugs could further improve the oncologic outcomes. Herein a narrative review is performed regarding the main rationale in combining immunotherapy and target therapies with SBRT looking at the available clinical data in case of oligometastatic NSCLC, Melanoma and Kidney cancer. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 63 publications
(51 reference statements)
2
21
0
4
Order By: Relevance
“…Notably, brain metastases represent the main cause of death in melanoma patients [42]. Radiotherapy is frequently used to treat metastases, e.g., in the brain with stereotactic radiotherapy or bone with fraction regimens of 2 Gy up to a dose of 50 Gy [43][44][45][46][47]. Also, single symptomatic metastases can be irradiated if systemic treatment controls disease in the rest of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, brain metastases represent the main cause of death in melanoma patients [42]. Radiotherapy is frequently used to treat metastases, e.g., in the brain with stereotactic radiotherapy or bone with fraction regimens of 2 Gy up to a dose of 50 Gy [43][44][45][46][47]. Also, single symptomatic metastases can be irradiated if systemic treatment controls disease in the rest of the body.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, irradiating multiple lesions promoted promising effects when RT was combined with anti-PD-1 mAb in patients with a range of metastatic solid tumors [ 48 ]. Another report indicated that, in the context of oligometastases, ablative doses of RT together with IO agents improved the control rates of cancers including melanoma, NSCLC, and kidney cancer [ 49 ]. A study from Gomez et al supported the potentially curative approach of irradiating all lesions as standard of care for patients with oligometastatic NSCLC [ 50 ].…”
Section: The Potential Effects Of Radiotherapy Treatment Volumes Omentioning
confidence: 99%
“…Les résultats des combinaisons de RT à haute dose et d'immunothérapie ont récemment été publiés dans une revue narrative [31]. Dans le cadre du mélanome, seules des études rétrospectives sont présentées.…”
Section: Données D'activité Des Immunothérapies Dans Les Maladies Oliunclassified
“…Les mêmes auteurs [31] ne sélectionnent que quelques cas cliniques intéressants de cancers du rein suggérant qu'immunothérapie et SBRT pourraient avoir un intérêt dans le contrôle tumoral. Une récente étude rétrospective incluant seulement 20 patients a regardé l'effet de la RT chez des patients traités par nivolumab, faisant la distinction entre SBRT à visée ablative (dose biologique équivalente (BED) > 50 Gy) pour des maladies oligoprogressives et RT à visée symptomatique [33].…”
Section: Données D'activité Des Immunothérapies Dans Les Maladies Oliunclassified
See 1 more Smart Citation